2011
DOI: 10.1002/qj.815
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance mechanisms for the early‐morning maximum summer rainfall over southeast China

Abstract: During the summer months, diurnal rainfall variation over southeast China is frequently characterized by a major peak in the afternoon and a minor peak in the early morning. While the afternoon rainfall maximum is generally recognized to be mainly modulated by the diurnally varying wind introduced by land-sea and mountain-valley differential heating, causes of the early-morning rainfall are not well documented. In this study, variation in the semi-diurnal harmonic of rainfall is found to be more important than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 32 publications
(62 reference statements)
0
22
0
Order By: Relevance
“…Meanwhile, mechanisms behind S2 cycle have rarely been discussed partly due to low temporal resolution of precipitation data to resolve the S2 harmonic. Nevertheless, Dai (), for instance, found that the S2 cycle is more significant over the oceans and consistent with the phase of semidiurnal atmospheric tides, and Huang and Chan () proposed that the S2 variation over southeast China is induced by land–sea differential heating.…”
Section: Methodsmentioning
confidence: 88%
“…Meanwhile, mechanisms behind S2 cycle have rarely been discussed partly due to low temporal resolution of precipitation data to resolve the S2 harmonic. Nevertheless, Dai (), for instance, found that the S2 cycle is more significant over the oceans and consistent with the phase of semidiurnal atmospheric tides, and Huang and Chan () proposed that the S2 variation over southeast China is induced by land–sea differential heating.…”
Section: Methodsmentioning
confidence: 88%
“… Lin et al, 2011]; this, however, cannot explain the decline in sea breeze over other regions. In view of previous studies [e.g., Huang and Chan , ], it is known that the increase in thermal instability (i.e., normaldTnormaldz>0; thermal trigger) can help induce upward motions and low‐level wind convergence. Because Taipei has warmed considerably more than other stations over the past five decades [ Shiu et al, ; Weng , ; Hsu et al, ; Lu et al, ], it is hypothesized that its related thermal instability change is different from other subregions', and such difference in thermal instability may help explain the observed regional difference in Figure c.…”
Section: Resultsmentioning
confidence: 99%
“…The TRMM 3B42 data provides rain rate at the spatial resolution of 0.25° longitude × 0.25° latitude, comparable with the common meteorological station network spacing in the East Asian summer monsoon region (Zhou et al 2008). TRMM 3B42 data has recently been proven to be a good proxy for diurnal convection over the East Asian regions (Hong et al 2005;Huang and Chan 2011).…”
Section: Observational Datamentioning
confidence: 70%
“…Many studies examining the observational data have noted that the summer continental diurnal rainfall generally peaks in the late afternoon (Ramage 1952;Yin et al 2009;Huang et al 2010;Huang and Chan 2011), while the oceanic diurnal convection tends to reach its maximum in the early morning (Kraus 1963;Andersson 1970). It was suggested that such diurnal rainfall evolution over the continental regions cannot be simulated well by most of the global climate models (Dai 2006;Hara et al 2009).…”
Section: Introductionmentioning
confidence: 99%